Prevalence of Toxoplasmosis of Males Blood Donors in Baghdad - Mahmood, Suhad; AL-Qadhi, Ban; Zghair, Khawla (Iraqi Journal of Science, 2024)
Toxoplasma gondii is intracellular parasites, which infect a large proportion of the world’s population, but uncommonly causes clinically significant disease .The present study was performed to estimate the prevalence of toxoplasmosis in Iraqi male. Venous blood samples were collected from healthy male age between (18-57) years attended the National blood transfusion centre in Baghdad from Oct, 2011 to Jan. 2012. Latex agglutination test (LAT) and Enzyme linked Immunosorbant Assay (ELISA), were used to detect anti-Toxoplasmosis IgM and IgG antibodies. The results showed significant differences between seropositive toxoplasmosis infections between LAT, 136/400 (34%) and ELISA - IgG, 121/400 (30.25%). The blood group phenotypes of the infected male blood donors high light the role in toxoplasmosis infection and the AB blood group characterized by the highest significant percentage of infection. Chronic and actue toxoplasmosis infection in married males included in this study was significantly higher, 101(83.47%) and 7(70%) respectively than unmarried males 20 (16.52%) and 3(30%) respectively. However married males showed significant difference between fertile and infertile infected males, they were 31(30.69%), 6(85.71%) and 70 (69.30%), 1 (14.28%) by ELISA IgG and IgM respectively. Private worker males revealed highly significant percentages of chronic and acute toxoplasmosis 91(75.20%), 2(20%) respectively compared with government worker, 30(24.79%), 8 (80%) respectively. Chronic seropositive toxoplasmosis was higher in males inhabited rural regions, 111(91.73%), than in males inhabited urban regions, 10(8.26%.